2020
DOI: 10.3390/cancers12092556
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wnt/β-Catenin Inhibition on Cell Proliferation through CDC25A Downregulation in Soft Tissue Sarcomas

Abstract: The Wnt signaling pathway is an important cellular mechanism for regulating differentiation processes as well as cell cycle events, and different inhibitors of this pathway, for example, PRI-724, are showing promising results in clinical trials for treatment of advanced pancreatic adenocarcinoma or ovarian cancer. Growing evidence suggests that Wnt signaling may also be crucial for tumorigenesis and progression of soft tissue sarcomas (STS), a malignant neoplasm with few therapeutic options at an advanced stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
(85 reference statements)
0
18
0
Order By: Relevance
“…Preclinical studies showed that PRI-724, the second-generation of CBP/catenin antagonist, inhibited cell proliferation and reduced cell growth in a variety of cancer types, including neuroendocrine tumors [ 48 ], osteosarcoma [ 54 ], head and neck carcinoma [ 55 ], hepatocellular carcinoma [ 56 ] and also in soft tissue sarcomas [ 57 ]. Similarly to LGK974, we showed that GCT cell lines were sensitive to PRI-724 in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical studies showed that PRI-724, the second-generation of CBP/catenin antagonist, inhibited cell proliferation and reduced cell growth in a variety of cancer types, including neuroendocrine tumors [ 48 ], osteosarcoma [ 54 ], head and neck carcinoma [ 55 ], hepatocellular carcinoma [ 56 ] and also in soft tissue sarcomas [ 57 ]. Similarly to LGK974, we showed that GCT cell lines were sensitive to PRI-724 in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the significant efficacy of PRI-724 treatment in NTERA-2 CisR cells, we tried to further sensitize these cells using a combined treatment approach with cisplatin. Previous studies of combined treatments with PRI-724 showed its ability to enhance the cytotoxic effect of chemotherapeutic drugs in platinum-resistant ovarian cancer cells [ 65 ] as well as in soft tissue sarcomas [ 57 ]. Our in vitro data showed synergistic effect only when higher PRI-724 concentrations were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICG‐001 and C‐82 are CBP inhibitors. They are also metabolites of PRI‐724, which is under clinical trials for its antitumor activity, 227 they inhibited fibrosis via Wnt/β‐Catenin signaling, with ICG‐001 showing great efficacy in upregulating apoptosis and inhibiting migration as well as C‐82 showing potent inhibition of proliferation and cell viability 106 …”
Section: Potential New Pharmaceuticals and Their Target‐signaling Pathwaysmentioning
confidence: 99%
“…The study demonstrated that PRI-724 significantly reduces cell proliferation of different subtypes of STS cell lines in vitro by downregulating the expression of the WNT target gene CDC25A , which is highly expressed in STS patient samples, thereby inducing cell death or cycle arrest. Most importantly, combination of PRI-724 with standard STS chemotherapeutic drugs, DXR or trabectedin, enhanced their antitumor activity in a synergistic manner, suggesting that this new strategy with PRI-724 could also have a beneficial clinical effect on patients with STS [ 196 ]. These results are a basis for future clinical trials evaluating inhibitors of β-catenin–co-activator interactions in STS patients with an activated Wnt signaling pathway, the latter being a novel selection criterion that could be included when recruiting patients.…”
Section: Targeting Wnt Signaling Pathway In Stsmentioning
confidence: 99%